Current challenges in managing comorbid heart failure and COPD. (2nd September 2018) - Neder, J. Alberto; Rocha, Alcides; Alencar, Maria Clara N.; Arbex, Flavio; Berton, Danilo C.; Oliveira, Mayron F.; Sperandio, Priscila A.; Nery, Luiz E.; O'Donnell, Denis E.
ABSTRACT: Introduction : Heart failure (HF) with reduced ejection fraction and chronic obstructive pulmonary disease (COPD) frequently coexist, particularly in the elderly. Given their rising prevalence and the contemporary trend to longer life expectancy, overlapping HF–COPD will become a major cause of morbidity and mortality in the next decade. Areas covered : Drawing on current clinical and physiological constructs, the consequences of negative cardiopulmonary interactions on the interpretation of pulmonary function and cardiopulmonary exercise tests in HF–COPD are discussed. Although those interactions may create challenges for the diagnosis and assessment of disease stability, they provide a valuable conceptual framework to rationalize HF–COPD treatment. The impact of COPD or HF on the pharmacological treatment of HF or COPD, respectively, is then comprehensively discussed. Authors finalize by outlining how the non-pharmacological treatment (i.e. rehabilitation and exercise reconditioning) can be tailored to the specific needs of patients with HF–COPD. Expert commentary : Randomized clinical trials testing the efficacy and safety of new medications for HF or COPD should include a sizeable fraction of patients with these coexistent pathologies. Multidisciplinary clinics involving cardiologists and respirologists trained in both diseases (with access to unified cardiorespiratory rehabilitation programs) are paramount to decrease the humanitarian and social burden of HF–COPD.